2021
DOI: 10.1016/j.ijpharm.2021.120701
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide inhalation powder made by thin-film freezing: Multi-dose tolerability and exposure in rats and pharmacokinetics in hamsters

Abstract: In this work, we have developed and tested a dry powder form of niclosamide made by thin-film freezing (TFF) and administered it by inhalation to rats and hamsters to gather data about its toxicology and pharmacokinetics. Niclosamide, a poorly water-soluble drug, is an interesting drug candidate because it was approved over 60 years ago for use as an anthelmintic medication, but recent studies demonstrated its potential as a broad-spectrum antiviral with pharmacological effect against SARS-CoV-2 infection. TFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…This study demonstrated that the co-formulation of niclosamide with lysozyme is four-fold more potent against coronaviruses compared to niclosamide alone. In a recent study, Jara et al [ 77 ] developed a dry powder formulation of niclosamide in combination with hydrophilic excipients, mannitol and leucine, using a thin-film freezing method. These powders showed acceptable aerosol properties, with a fine particle fraction of 86%, suitable for deep lung delivery.…”
Section: Inhaled Covid-19 Therapeuticsmentioning
confidence: 99%
“…This study demonstrated that the co-formulation of niclosamide with lysozyme is four-fold more potent against coronaviruses compared to niclosamide alone. In a recent study, Jara et al [ 77 ] developed a dry powder formulation of niclosamide in combination with hydrophilic excipients, mannitol and leucine, using a thin-film freezing method. These powders showed acceptable aerosol properties, with a fine particle fraction of 86%, suitable for deep lung delivery.…”
Section: Inhaled Covid-19 Therapeuticsmentioning
confidence: 99%
“…Intranasal administration of niclosamide (0.24 mg·kg −1 ·day −1 ) to SARS-CoV-2-infected mice for 10 days improved survival and significantly reduced viral loads. 538 Darunavir, with a similar anti-HIV effect, belongs to the carbamates. 539 Computational evidence showed it may interact with the M pro pocket.…”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 99%
“…Niclosamide, an anthelmintic drug that was repurposed for COVID-19 as a tablet, was reformulated for inhaled delivery for COVID-19. In one study, Jara et al ( Jara et al, 2021 ) developed niclosamide dry powder by TFF technology. Mannitol and L-leucine were in this study to enhance the aerosolization property of the prepared dry powder.…”
Section: Reformulation Of Anti-sars-cov-2 Agents As Inhalable Formmentioning
confidence: 99%